Effect of sevoflurane postconditioning on myocardial oncosis and autophagy in ischemia-reperfusion injury in isolated rat heart (Bangladesh Journal of Pharmacology, 2018)
The effects of sevoflurane postconditioning on myocardial oncosis and autophagy were studied in 32 isolated rat heart of ischemia-reperfusion injury. The hearts were perfused by: a) Sham surgery group, b) simple sevoflurane group, c) simple ischemia-reperfusion group (I/R) group, and d) sevoflurane postconditioning group. The ratios between the gray density values of the target bands to the gray density value of GADPH were used to reflect the Beclin-1, LC3II/I, and porimin expression levels. The LC3II/I level in the sevoflurane postconditioning group was lower than the level in the I/R group. The porimin level in the sevoflurane postconditioning group was lower than the level in the I/R group. The myocardial infarction range in the sevoflurane postconditioning group (33 ± 5%) was significantly diminished compared with the range in the I/R group (53 ± 6%) (p